LncRNA-PVT1 enhances glucose metabolism of pediatric low-grade glioma cells through sponging miR-187-3p - Beibei Li; Zijian Feng; Yanyan Zheng (Polish Journal of Pathology)
Pediatric low-grade glioma (PLGG) is a heterogeneous group of primary central nervous system malignancies which represent the most frequent brain tumors in children. Although diagnosis and treatment of PLGG have been improved recently, the molecular mechanisms underlying the oncogenesis and progression of PLGG remain elusive. Studies have revealed critical roles of long non-coding RNAs (lncRNAs) in brain tumor progressions. Here, we aimed to investigate the clinical roles and molecular mechanisms of lncRNA PVT1 in PLGG. Expression of PVT1 was significantly upregulated in PLGG tissues compared with normal brain tissues. Blocking PVT1 effectively suppressed the glucose metabolism of PLGG-derived cells. MicroRNA-187-3p was detected to be remarkedly downregulated in PLGG tissues. Moreover, miR-187-3p is negatively correlated with PVT1 in PLGG tissues. We identified PVT1 sponged miR-187-3p to block its expression in PLGG cells. This association was further verified by RNA pull-down and luciferase assay. Subsequently, rescue experiments validated that inhibition of miR-187-3p in PVT1-silenced PLGG cells successfully overcame the low-PVT1-induced miR-187-3p upregulation and glucose metabolism. In summary, this study reports critical roles and molecular mechanisms of the lncRNA PVT1-accelarated glucose metabolism of PLGG cells.